Enhancing peptide and PMO delivery to mouse airway epithelia by chemical conjugation with the amphiphilic peptide S10 - Maud Auger; Luis Sorroza-Martinez; Nadine Brahiti; Carole-Ann Huppé; Laurence Faucher-Giguère; Imen Arbi; Maxime Hervault; Xue Cheng; Bruno Gaillet; Frédéric Couture; David Guay; Al-Halifa Soultan (Elsevier, 2024)
Delivery of antisense oligonucleotides (ASOs) to airway epithelial cells is arduous due to the physiological barriers that protect the lungs and the endosomal entrapment phenomenon, which prevents ASOs from reaching their intracellular targets. Various delivery strategies involving peptide-, lipid-, and polymer-based carriers are being investigated, yet the challenge remains. S10 is a peptide-based delivery agent that enables the intracellular delivery of biomolecules such as GFP, CRISPR-associated nuclease ribonucleoprotein (RNP), base editor RNP, and a fluorescent peptide into lung cells after intranasal or intratracheal administrations to mice, ferrets, and rhesus monkeys. Herein, we demonstrate that covalently attaching S10 to a fluorescently labeled peptide or a functional splice-switching phosphorodiamidate morpholino oligomer improves their intracellular delivery to airway epithelia in mice after a single intranasal instillation. Data reveal a homogeneous delivery from the trachea to the distal region of the lungs, specifically into the cells lining the airway. Quantitative measurements further highlight that conjugation via a disulfide bond through a pegylated (PEG) linker was the most beneficial strategy compared with direct conjugation (without the PEG linker) or conjugation via a permanent thiol-maleimide bond. We believe that S10-based conjugation provides a great strategy to achieve intracellular delivery of peptides and ASOs with therapeutic properties in lungs.